UPAYA PENINGKATAN KOMITMEN PROFESI DOSEN (STUDI EMPIRIS MENGGUNAKAN SQUENTIAL EXPLANATORY DI FKIP UNIVERSITAS PAMULANG) - Saiful Anwar; Lodya Sesriyani; Rusmaini Rusmaini (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
The main problem in this study is that the commitment of lecturers to the profession still varies as can be seen from the fact that most of the lecturers still have the functional position of expert assistant. The purpose of this research is to see what variables have an influence on commitment to the teaching profession. The research method used is sequential explantory and optimizes quantitative descriptive findings using the SITOREM concept. based on research results obtained research results 1) there is an influence of the quality of work life on lecturer professional commitment; 2) there is an effect of self-efficacy on lecturer professional commitment, 3) Based on the results of SITOREM, it was found that of the five indicators of the quality of work life, there are three indicators that need to be improved, namely (job design, work balance, health, stress & safety) and indicators Self-efficacy that must be improved is (performance exposure, self-instructed performance, attribution and relaxation biofeedback) to increase the commitment of the teaching profession